REFLECTION OF RELAY-LEMB WAVES FROM THE END OF THE HEMISPHERE WITH MIXED BOUNDARY CONDITIONS - Gorodetska , Natalia; Starovoit , Inna; Shcherbak , Tatiana (Science-based technologies, 2021)
The article is devoted to the analysis of the wave field, which is excited when the first normal propagating wave is reflected from the end of the elastic hemisphere, part of which is rigidly clamped, and part is free from stresses. The boundary value problem belongs to the class of mixed boundary value problems, the characteristic feature of which is the presence of a local feature of stresses at the point of change of the type of boundary conditions.